Habilidades adquiridas por meio do esporte e sua transferência para o contexto da vida de atletas de voleibol - Mizoguchi, Marcus Vinícius (2018)
This study aimed to investigate the skills acquired through sport and the transfer process to life context in volleyball players. The first article developed a systematic review using database as Pubmed, SportDiscus, Web of Science, PsycINFO, Science Direct and Scielo, to review the state of art of life skills studies in sport context, acquiring 31 articles, based on inclusion and exclusion criteria. The results revealed a predominance of studies in Canada, United States, United Kingdom, and Australia, where a large group of programs focused of positive youth development was located. It was also verified that literature has evaluated several specifics psychologicals variables and how they are used in other contexts of life with few studies evaluating the transfer process and interventions for differents sports. The second article aimed to analyze the perception of the athletes about their internal and external assets, looking to identify the direct and indirect strategies adopted by the coaches and the results (positive and negative), that were present along their development of life skills in sport contexts. Thirteen volleyball players participated in the study, who played for the Brazilian National Team. It was applied a sociodemografic record and a retrospective semi-structured interview, using elements presented in the Model of coaching life skills through sport. Thematic and content analysis were performed to categorize emerging themes and first and second orders. The results demonstrated the importance of the personal characteristics and motor experiences, as well as external agents in athlete?s life in the beginning of practices, being important for the intervention of the coaches practices. During their sport experiences in Volleybal, the team actions (charge, goals and maturity), the environment actions (media, idols and clubs) and the coaches actions (oportunities, charges and teaching) are important to learn intelectual, physical and psychological skills used in the athlete?s life. The third aimed to study the process of transfer life skills of athletes on the coaches perceptions. Six coaches were interviewed, who were considered the most important coaches in the National Team athletes? lives. Semi-structured retrospective interviews were conducted based on the Model of coaching life skills through sport. Thematic and Content analysis were performed to obtain the results, creating emerging categories and themes. The results showed the concern of the coaches about the internal and external assets around the practitioners, developing motivational activities. It was not possible to identify a predominant coaches? characteristics, however, being acessible, relateness, leadership, and demand discipline were present during interation with the players. The fourth article sought to elaborate an exploratory model of the process of life skills transfer for sport contexts. Four components were reported, highlighting the last one, which classified the process of life skills transfer. Context Process and Individual Psychological Process were reported as importants factors in the transfer of behavior and attitudes learned in sport to other environments of life